Periodontal problems in menopausal women - Musyt, Wiktoria; Dudziński, Szymon; Pietruszka, Wiktoria; Klasicki, Przemysław (Journal of Education, Health and Sport, 2025)
Introduction: Menopause is a critical period marked by hormonal changes that significantly impact oral health. Estrogen deficiency alters the oral microbiome, increases the risk of periodontal diseases, and contributes to xerostomia and Burning Mouth Syndrome (BMS). Additionally, postmenopausal women undergoing bisphosphonate therapy for osteoporosis face a higher risk of osteonecrosis of the jaw (ONJ), particularly after extractions or implant placement. Aim: This study evaluates the impact of menopause on periodontal health, oral microbiome changes, xerostomia, BMS, ONJ, and dental implant success. Materials and Methods : A literature review was conducted on menopause-related periodontal diseases, microbiome alterations, salivary dysfunction, and complications affecting dental treatments using PubMed, Web of Science, and Google Scholar databases. A total of 54 articles were selected for analysis. Results: Menopausal women are more susceptible to periodontal diseases and oral discomfort due to microbiome shifts and reduced immune response. ONJ risk is heightened in bisphosphonate users, while delayed bone remodeling may affect implant success. Conclusions: Menopause-related oral health issues require early diagnosis and tailored treatment strategies. A proactive approach to periodontal care, salivary dysfunction, and implant planning is essential to maintaining oral health and improving quality of life.